Workspace management in corporate real estate of financial institution office premises and its correlation with performance / Nurul Sahida Fauzi, Abdul Hadi Nawawi and Yuhadi Sanuddin - Fauzi, Nurul Sahida; Nawawi, Abdul Hadi; Sanuddin, Yuhadi (2012)
Workspace management is an important element in Corporate Real Estate Management (CREM). It involves the process of strategic planning, managing and evaluating. Poor workspace management planning will affect the performance of the organization. However, studies on workspace management affecting financial institution office premises in the Malaysian banking industries have yet to be widely carried out in Malaysia. Furthermore, as financial institutions are unique and have their own characteristics, it is essential to create CREM for all financial institutions. The aim of this research described in this paper is to find the relationship between workspace management and performance. The research was based on interviews and survey on all CRE managers in financial institution office premises in Klang Valley area. The objectives of this study are (1) to analyse the most important factors in successful workspace management and (2) to investigate the correlation between the factors considered in workspace management and the performance of the financial institution office premises. Thirty five variables involving five factors, which are physical factors, non-physical factors, collaboration factors, work process factors, and health and safety factors. Computer screen (mean=4.62) is the most important variable in designing workspace in the office premises followed by the highest four among the ranking, which are mostly from physical factors and non-physical factors. The results show desktop layout (mean=4.57), keyboard placement (mean=4.52), cleanliness (mean=4.52), chairs (mean=4.48) and tables (mean=4.48). The results from the analysis show, office equipment such as chairs, tables, keyboard placement, computer screen placement, desk top layout, cleanliness, light control, workstation layout provide privacy, adequate meeting rooms, appropriate discussion rooms, and the work station layout suitable for employees work process are the most important factors that should be taken into consideration when designing workspace in the office premises and giving a big impact towards performance. All these variables are from four important factors which are physical factors, non-physical factors, collaboration factors and work process factors. However, health and safety factors show low importance in designing workspace management and influencing performance in financial institution office premises.